Patient Satisfaction Regarding Hospital Services in A Tertiary Level Hospital of Chitwan - Bhusal, Mina Kumari; Regmi, Kamala; Paudel, Madhu Maya; Adhikari , Pratima; Parajuli, Sumitra (Journal of Bharatpur Hospital, 2025)
Background Patient satisfaction is an important component of evaluating care. Patient satisfaction describes how patients value and regard their care. Patients' satisfaction with health care services is becoming an essential factor in health promotion. When patients are satisfied with healthcare services, it will enhance their quick recovery. Therefore, the study objective was to assess the patient’s satisfaction level in the tertiary-level Hospital. Methods A descriptive cross-sectional study was carried out among purposively selected 335 Patients and visitors from five wards of Bharatpur Hospital, Chitwan. Data was collected using a semi-structured interview schedule that included a Five-Point Likert Scale questionnaire. Informed written consent was obtained to ensure their rights. Data were analyzed in SPSS 22 version using descriptive and inferential statistics. Results The study findings revealed that 94% of participants were satisfied with hospital services with a mean value of 3.79±0.463. The highest satisfaction score was found regarding doctors’ care (4.04± 0.74), followed by nursing care (3.93± 0.577), and low satisfaction with hospital policy (3.66±0.655). There is no significant association between sociodemographic characteristics and patient satisfaction. The most frequently recommended areas for improvement were sanitation and cleanliness (15.48%), followed closely by improvement of physical facilities (14.83%) and crowd management (14.19%). Conclusions Almost all of the participants were satisfied with hospital services. Satisfaction with the care of doctors and nurses was high, and low satisfaction with hospital policy. It is recommended for the hospital management to enhance the hospital policy, cleanliness and facilities of the toilets and bathrooms.